IMPROVING THE METHODOLOGY OF STUDENTS' TEACHING OF SOCIAL AND HUMANITARIAN SCIENCES BASED ON A COMPETENT APPROACH (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article discusses the development of skills to eliminate deviations from the norm in fulfilling socio-pedagogical requirements, as well as preparing them for effective organization of scientific-pedagogical research from a practical point of view. Thorough mastering of the fundamentals of educational science requires students to fully analyze and synthesize the existing situation, to study all the factors that influence the origin of defects, to take a critical approach to solving the problem, to choose effective methods and methodologies, develops the skills of their purposeful use. Different levels of professional competence of teachers, different age, physiological and psychological capabilities of students, inability of certain, in particular, a group of students to learn subjects in the process of teaching and upbringing, social problems in them - creates problems such as observation of deviations from the norm in the fulfillment of pedagogical requirements. At the end of the 19th century and the beginning of the 20th century, a series of researches were carried out in the field of psychology. As a result, the theory of "psychological diagnosis" was founded in the first decades of the 20th century, and the theory of "pedagogical diagnosis" in the last decades. The main idea and research direction of these theories is the analysis and assessment of the quality of education based on the diagnosis of the real situation. He showed the necessity of teaching the educational subject "Pedagogical diagnosis and correction" at the Higher Education Institution. The purpose of the academic discipline "Pedagogical diagnosis and correction" is to create the necessary conditions for the comprehensive development of the student's personality, education, psychologically effective preparation for educational and professional activities based on the identification and use of pedagogically important information.